Effect of Chicken Bone Extract Powder on Epididymal Sperm Quality of Male Wistar Rats - Kakanang Buranaamnuay; A Kettawan; C Changsangfa; S Aiemongkot (Jurnal Ilmu Ternak dan Veteriner, 2021)
Calcium is one of the minerals that are essential for male reproductive function. Calcium deficiency adversely affects spermatogenesis, normal sperm function and results in infertility. The sperm quality of rats fed a standard diet containing chicken bone extract powder (BEP) was assessed in the present study. Twenty male 8-week-old rats, Wistar strain, were randomized by weight into two groups of ten rats each and fed ad libitum a standard diet containing calcium carbonate (CaCO3, control) or chicken BEP;  both were equivalent to 0.5% calcium. At the end of the 7-week consumption, the net body weight gains measured in control (101.33±21.81 g) and chicken BEP groups (100.74±26.80 g) were not significantly different (P>0.05). The in vitro sperm quality in terms of concentration, motility, viability, resistance to hypotonic stress, acrosomal reaction ability and morphology was comparable between control and chicken BEP (all were P>0.05). The results suggest that chicken BEP addition into feeds is an alternative calcium source that is as effective but less expensive as CaCO3, a commercial calcium (fortificant). At least, it has no detrimental effect on male reproductive function.